Student views on strategies to promote sustained learning in distance learning: An Ubuntu perspective (Teacher Education through Flexible Learning in Africa (TETFLE), 2023)
Distance learning in South Africa has been experiencing the unfortunate occurrences of low student throughput and retention. Therefore, the purpose of this paper was to determine possible strategies for sustained learning. Framed by Ubuntu as its theoretical perspective, the researchers discovered valuable insights through a methodological literature review and an empirical inquiry. Eight undergraduate students reflected on their distance learning experiences and challenges and suggested strategies for sustained learning. From an interpretivist research paradigm supported by a qualitative research approach, the study used a case study to conduct semi-structured interviews to gather data at an open distance learning institution in South Africa. The findings indicate that distance education institutions should provide sufficient learning support; conduct surveys to determine student challenges and needs; improve communication with students; develop a hotline; use open education resources and provide financial aid to all disadvantaged students. The study argues that the values of Ubuntu as set out in this paper, should be considered when drafting policy and implementing strategies to support students
Keywords: distance learning; challenges; strategies for sustained learning; student support; Ubuntu